Women across Asian art selected essays in art and material culture - Lu, Ling-En; Peyton, Allysa B. (David A. Cofrin Asian art manuscript series, 2023)
"Filled with exquisite color illustrations, this volume examines an underserved aspect of Asian art history by discussing women artists, collectors, archaeologists, and architects. The essays in Women across Asian Art cover a wide geographical area, from Japan to Pakistan, as they draw attention to people whose efforts have largely been left out of scholarship"--